Kutub Al-Lughah Al-Arabiyyah Al-Muqarrarah Li Thalabah Al-Madrasah Al-Mutawassithah Al-Islamiyyah: Dirasah Tanqihiyah Min Haitsu Al-Mawad Wa At-Taqdim - Afif Amrullah; Maslathif Dwi Purnomo (Institut Agama Islam Negeri (IAIN) Metro, 2022)
This research addresses the existing problems around the materials of the Arabic language textbooks entitled